Gonadotropin-Releasing Hormone (GnRH) Activates the M-Current in GnRH Neurons: An Autoregulatory Negative Feedback Mechanism? - Xu, Chun (The Endocrine Society, 2008)
GnRH autoregulates GnRH neurons through an ultrashort feedback loop. One potential mechanism is the regulation of K(+) channel activity through the GnRH receptor. Whereas GnRH inhibits the activity of the M-current in peripheral neurons, there is no direct evidence that the M-current is involved in the autoregulatory pathway of GnRH or if the M-current is expressed in GnRH neurons. The M-current is a noninactivating, subthreshold K(+) current that inhibits cell excitability and is ubiquitously expressed in the central nervous system. We found that GnRH neurons expressed the neuronal M-current subunits, KCNQ2, -3, and -5 in addition to GnRH receptor (GnRH R1). Therefore, using whole-cell patch clamp recording and single-cell RT-PCR, we explored the effects of mammalian GnRH peptide on enhanced green fluorescent protein-tagged GnRH neurons acutely dispersed as well as in slice preparations. GnRH (100nm) inhibited GnRH neuronal excitability by hyperpolarizing the membrane. In the presence of CdCl(2), BaCl(2), and tetrodotoxin, GnRH activated an outward current in a dose-dependent manner (EC(50) 11 nm) in 30% of GnRH neurons. In voltage clamp, the selective M-channel blocker, XE-991, inhibited a K(+) current in GnRH neurons. XE-991 also antagonized the outward K(+) current induced by GnRH. Moreover, the GnRH effects on the M-current were blocked by the GnRH R1 antagonist antide. Therefore, these findings indicate that GnRH activates the M-current in a subpopulation of GnRH neurons via GnRH R1. This ultrashort circuit is one potential mechanism by which GnRH could modulate its own neuronal excitability through an autoreceptor.